Exploring Nanoscale Lubrication Mechanisms of Multilayer MoS2 During Sliding: The Effect of Humidity - Claerbout, Victor E. P.; Nicolini, Paolo; Polcar, Tomas (Frontiers in Chemistry, 2021)
Solid lubricants have received substantial attention due to their excellent frictional properties. Among others, molybdenum disulfide (MoS2) is one of the most studied lubricants. Humidity results in a deterioration of the frictional properties of MoS2. The actual mechanism at the nanoscale is still under debate, although there are indications that chemical reactions are not likely to occur in defect-free structures. In this study, we performed nonequilibrium molecular dynamics simulations to study the frictional properties of multilayer MoS2 during sliding in the presence of water. Moreover, we also investigated the effect of sliding speed and normal load. We confirmed earlier results that a thin layer of water organizes as a solidified, ice-like network of hydrogen bonds as a result of being confined in a two-dimensional fashion between MoS2. Moreover, we found that there exists an energy-driven, rotational dependence of the water network atop/beneath MoS2. This orientational anisotropy is directly related to the dissipative character of MoS2 during sliding. Finally, three distinct frictional regimes were identified, two for a thin layer of water and one for bulk water. In the case of a thin layer and low coverage, water represents a solid-like contaminant, causing high energy dissipation. For a thin layer and high coverage, water starts to act as a solid-like lubricant, reducing dissipation during sliding. Finally, a regime where water acts as a liquid lubricant, characterized by a clear velocity dependence was found.